A Model to Enhance Students Intention to Adopt and use Mobile Learning in Ugandan Universities (Global Journal of Management and Business Research, 2016)
M-learning systems have become the order of the day for universities in countries like Uganda to conduct studies to their students. The main attention towards M-learning is the increase in the number of mobile devices such as mobile phones, PDAs, Smart Phones, laptops, and iPads as well as enhancements in the technological capabilities of these devices. The purpose of this study was to develop a model to enhance students#x2019; intention to adopt and use mobile learning. A number of factors have hindered the adoption and use of M-learning. Various solutions have been put forward but they have not adequately addressed the issue of adoption and use of M-learning in Ugandan Universities. In developing countries, M-learning adoption and use is also constrained by lack of information about its requirements. The need therefore remains, to determine requirements and customize existing M-learning adoption models to suit the needs of universities in developing countries.
Keywords: m-learning; adoption and use; students#x2019; intention; m-learning systems